Hodi Zarifov - Textual Scholar - Barno Mirzaeva (Researchparks Publishing, 2022)
Scientific principles of preparation of works of Uzbek folklore for publication are considered to be one of the priority criteria of work from recording works of folk art to publication. This article discusses the significance of Hodi Zarifov's article